2021
DOI: 10.1103/physrevb.103.024411
|View full text |Cite
|
Sign up to set email alerts
|

Generation of spin waves via spin-phonon interaction in a buried dielectric thin film

Abstract: In this paper, we investigate the magnetic, optical, and lattice responses of a Pt/Cu/Bi 1 Y 2 Fe 5 O 12 /Gd 3 Ga 5 O 12 heterostructure to femtosecond laser excitation of the opaque Pt/Cu metallic bilayer. The electronic excitation generates coherent and incoherent phonons, which trigger high-frequency standing spin waves (SWs) in the dielectric Bi 1 Y 2 Fe 5 O 12 layer via a phonon-induced change of magnetic anisotropy. We find that the incoherent phonons (heat) can induce a fast (<1ps) and slow (>1000 ps) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…According to Ref. 45, the oscillations amplitude of acoustic mode increases linearly with the laser energy density within the probed range. Moreover, the FeGa material with a thickness as thick as 60 nm is preferred to induce an obvious magnetoelastic behavior [46], while 10 nm at the present experiment is probably too thin.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…According to Ref. 45, the oscillations amplitude of acoustic mode increases linearly with the laser energy density within the probed range. Moreover, the FeGa material with a thickness as thick as 60 nm is preferred to induce an obvious magnetoelastic behavior [46], while 10 nm at the present experiment is probably too thin.…”
mentioning
confidence: 89%
“…Besides, FeGa alloys are particularly interesting because of their magneto-elastic properties [44]. The acoustic waves are possible to be triggered by ultrashort laser and as a result, spin precession would be excited non-thermally via a magnetoelastic effect [45]. However, this effect can be excluded based on the following reasons: firstly, the external field has to be applied along with the hard axis of FeGa, otherwise, the magnetization precession cannot be induced.…”
mentioning
confidence: 99%
“…Since quantities of ions in the sublattices are in the ratio of 2 : 3 and an interaction between the sublattices is AFM, the magnetic structure turns out to be ferrimagnetic. Prominent magneto-optical characteristics [7] and extremely weak damping of spin waves [8] make IG the basis of various optoelectronic and promising spin-wave devices development [7,9,10].…”
mentioning
confidence: 99%
“…So far, this approach has attracted attention in two different ways: The first is related to controlling the magnetization dynamics with picosecond strain pulses generated in metallic film by femtosecond laser pulses [29][30][31][32][33]. It was demonstrated that a strain pulse can trigger a coherent magnetization precession in metal [29][30][31], semiconductor [32], and dielectric [33,34] magnetic films. Because of its long propagation distance of several millimeters combined with low energy losses [35,36], strain pulses offer an important opportunity to excite magnetization precession in magnetic materials deeply embedded in opaque heterostructure devices [32][33][34].…”
mentioning
confidence: 99%
“…It was demonstrated that a strain pulse can trigger a coherent magnetization precession in metal [29][30][31], semiconductor [32], and dielectric [33,34] magnetic films. Because of its long propagation distance of several millimeters combined with low energy losses [35,36], strain pulses offer an important opportunity to excite magnetization precession in magnetic materials deeply embedded in opaque heterostructure devices [32][33][34]. The second way is related to control the lattice strain by the ultrafast modification of the magnetic order [14,23,[37][38][39][40][41].…”
mentioning
confidence: 99%